Micro-Environmental Stress Induces Src-Dependent Activation of Invadopodia and Cell Migration in Ewing Sarcoma - Bailey, Kelly M. (Neoplasia, 2016)
Metastatic Ewing sarcoma has a very poor prognosis and therefore new investigations into the biologic drivers of metastatic progression are key to finding new therapeutic approaches. The tumor microenvironment is highly dynamic, leading to exposure of different regions of a growing solid tumor to changes in oxygen and nutrient availability. Tumor cells must adapt to such stress in order to survive and propagate. In the current study, we investigate how Ewing sarcoma cells respond to the stress of growth factor deprivation and hypoxia. Our findings reveal that serum deprivation leads to a reversible change in Ewing cell cytoskeletal phenotypes. Using an array of migration and invasion techniques, including gelatin matrix degradation invadopodia assays, we show that exposure of Ewing sarcoma cells to serum deprivation and hypoxia triggers enhanced migration, invadopodia formation, matrix degradation and invasion. Further, these functional changes are accompanied by and dependent on activation of Src kinase. Activation of Src, and the associated invasive cell phenotype, were blocked by exposing hypoxia and serum-deprived cells to the Src inhibitor dasatinib. These results indicate that Ewing sarcoma cells demonstrate significant plasticity in response to rapidly changing micro-environmental stresses that can result from rapid tumor growth and from necrosis-causing therapies. In response to these stresses, Ewing cells transition to a more migratory and invasive state and our data show that Src is an important mediator of this stress response. Our data support exploration of clinically available Src inhibitors as adjuvant agents for metastasis prevention in Ewing sarcoma.